Basic Color Terms (BCTs) and Categories (BCCs) in Three Dialects of the Spanish Language: Interaction Between Cultural and Universal Factors - Lillo, Julio; González-Perilli, Fernando; Prado-León, Lilia; Melnikova, Anna; Álvaro, Leticia; Collado, José A.; Moreira, Humberto (Frontiers in Psychology, 2018)
Two experiments were performed to identify and compare the Basic Color Terms (BCTs) and the Basic Color Categories (BCCs) included in three dialects (Castilian, Mexican and Uruguayan) of the Spanish language. Monolexemic Elicited lists were used in the first experiment to identify the BCTs of each dialect. Eleven BCTs appeared for the Spanish and the Mexican, and twelve did so for the Uruguayan. The six primary BCTs (rojo ‘red’, verde ‘green’, amarillo ‘yellow’, azul ‘blue’, negro ‘black’ and blanco ‘white’) appeared in the three dialects. This occurred for only three derived BCTs (gris ‘gray’, naranja ‘orange’ and rosa ‘pink’) but not for the other five derived BCTs (celeste ‘sky blue’, marrón ‘brown’, café ‘brown’, morado ‘purple’ and violeta ‘purple’). Color transitions were used in the second experiment for two different tasks. Extremes naming task was used to determine the relation between two different dialects’ BCTs: equality, equivalence or difference. The results provided the first evidence for marrón ‘brown’ and café ‘brown’ being equivalent terms for the same BCC (BROWN in English) as is the case of morado ‘purple’ and violeta ‘purple’. Uruguayan celeste ‘sky blue’ had no equivalent BCT in the other two dialects. Boundary delimitation task required the selection of the color in the boundary between two categories. The task was used to reasonably estimate the volume occupied by each BCC in the color space considering its chromatic area and lightness range. Excluding SKY BLUE (celeste ‘sky blue’) and BLUE (azul ‘blue’), the other BCCs color volumes were similar across the three dialects. Uruguayan SKY BLUE and BLUE volumes conjointly occupied the portion of the color space corresponding to the Castilian and Mexican BLUE BCC. The fact that the BCT celeste ‘sky blue’ only appeared in Uruguayan very probably derived from specific cultural factors (the use of the color in the flags and the arrival of an important number of Italian immigrants). Nevertheless, these cultural factors seem to nurture from a perceptive structuring of the color space, which nature is universal, as the boundaries of this category can be delimited from the responses of Spanish and Mexican participants.